2016
DOI: 10.3390/ijerph13070704
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Trends in Childhood Asthma-Related Hospitalizations in Belo Horizonte, Minas Gerais, Brazil and Their Association with Social Vulnerability

Abstract: Introduction: Asthma is a multifactorial disease and a serious public health problem. Environmental factors and poverty are the main determinants of this disease. Objective: To describe the spatial and temporal distribution of asthma-related hospitalizations and identify the areas with the highest prevalence of and vulnerability to severe asthma in a major Brazilian city. Methods: An ecological study of hospitalizations for asthma from 2002 to 2012, in children and adolescents under 15 years of age, living in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
1
9
0
4
Order By: Relevance
“…The first study found that areas of Salvador whose population had lower levels of education and income, had a higher risk of hospitalisation for respiratory diseases, particularly for asthma and pneumonia 90. The second study conducted in Belo Horizonte found that hospital admissions for asthma were higher in areas of greater social vulnerability, suggesting that social and environmental factors may be determinants of variations in asthma prevalence 91…”
Section: Resultsmentioning
confidence: 99%
“…The first study found that areas of Salvador whose population had lower levels of education and income, had a higher risk of hospitalisation for respiratory diseases, particularly for asthma and pneumonia 90. The second study conducted in Belo Horizonte found that hospital admissions for asthma were higher in areas of greater social vulnerability, suggesting that social and environmental factors may be determinants of variations in asthma prevalence 91…”
Section: Resultsmentioning
confidence: 99%
“…While the domains included in measures are often quite similar, the actual indicators vary widely across countries. Education has been measured as literacy rate,22 heads of households with less than a year of education23 or entry to higher education 13. Alongside theory, country specific knowledge and the spatiotemporal context should guide the selection of indicators as deprivation is relative to what is customary to the societies in which people live 24.…”
Section: Developing Deprivation Measures: Stages and Optionsmentioning
confidence: 99%
“…Continued computational improvements have allowed researchers to build increasingly sophisticated spatial or spatio-temporal models [20][21][22][23]. Recent studies have employed Bayesian small-area statistical methods that can improve flexibility of models to incorporate structured and unstructured random effects in a hierarchical framework, such as a BHM [24][25][26].…”
Section: Spatio-temporal Bayesian Frameworkmentioning
confidence: 99%